Use of antiviral medications in drug reaction with eosinophilia and systemic symptoms (DRESS): A case of infantile DRESS. Issue 2 (15th January 2018) - Chow, Maggie L.; Kim, David; Kamath, Sonia; Peng, David; Luu, Minnelly
Abstract: A 3‐month‐old girl with Sturge‐Weber syndrome presented with a morbilliform rash, eosinophilia, and fulminant liver failure to our tertiary pediatric hospital. She was diagnosed with drug reaction with eosinophilia and systemic symptoms complicated by viremia and evidence of viral hepatitis on liver biopsy. We discuss the role of viral reactivation in drug reaction with eosinophilia and systemic symptoms and the relevance of antiviral therapy in management.